Studi Kualitas Air Krueng Brayeun di Kabupaten Aceh Besar sebagai Air Baku Air Minum - Ansiha Nur; Yeggi Darnas; Mhd. Fauzi (Jurnal Serambi Engineering, 2023)
This study aims to identify the water quality of the Krueng Brayeun River as one of the potential surface waters to meet the needs for the development of a Drinking Water Supply System (SPAM) in Banda Aceh City and Aceh Besar District. Water samples were taken at five locations around the planned intake, namely two points before the planned intake and three points after the planned intake. Laboratory tests were carried out on physical, chemical, and biological parameters. Based on the test results, it is possible to use the proposed intake location as a source of raw water for PP RI No. 22 of 2021 class I. There is no possibility of pollution at the site of the proposed intake, and water-related activities that are carried out close to bends do not have an impact on the river of quality Kr. Brayeun. Recommendations for securing raw water sources are needed so that the utilization of Krueng Brayeun River water does not interfere with the PDAM's processing process.